Pharmacological activities and gas chromatography–mass spectrometry analysis for the identification of bioactive compounds from Justicia adhatoda L. - Musa, Muhammad; Jan, Gul; Jan, Farzana Gul; Hamayun, Muhammad; Irfan, Muhammad; Rauf, Abdur; Alsahammari, Abdulrahman; Alharbi, Metab; Suleria, Hafiz A. R.; Ali, Niaz (Frontiers in Pharmacology, 2022)
The current study aimed to assess the pharmacological potential of Justicia adhatoda by evaluating the presence of biologically active compounds using the gas chromatography–mass spectrometry approach and to undertake biological activities for the effectiveness of the present compounds using standard tests. A total of 21 compounds were identified in the gas chromatography–mass spectrometry analysis of the ethyl acetate fraction in which 14 of the identified compounds are recognized for their pharmacological potential in the literature. In total, four fractions (ethyl acetate, chloroform, n-hexane, and aqueous) were evaluated for pharmacological activities. In carrageenan-induced inflammation, the chloroform fraction exhibited high anti-inflammatory activity (46.51%). Similarly, the analgesic potential of ethyl acetate fraction was the most effective (300 mg/kg) in the acetic acid-induced test. Similarly, in the formalin test, ethyl acetate fraction exhibited maximum inhibition in both early (74.35%) and late phases (88.38). Maximum inhibition of pyrexia (77.98%) was recorded for the ethyl acetate fraction (300 mg/kg). In DPPH assay, the ethyl acetate fraction revealed the highest scavenging potential among other fractions (50 μg/ml resulted in 50.40% and 100 μg/ml resulted in 66.74% scavenging).